Pengembangan Kompetensi Bahasa Asing Siswa SMPN 06 Lembang Jaya melalui Kegiatan Edukasi KKN - Nuzul Hidayat; Arif Permana Dalimunthe; Salwa Salsabilla Putri; Revina Anjelia; Zifatul Nisa Azizi; Indah Maharani; Aldava Mildli Koto; Kansus madai (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
The Community Service Program (KKN) is a form of student community service aimed at directly applying academic knowledge in the field. This article describes the implementation of a foreign language education program conducted by KKN students at SMPN 06 Lembang Jaya. The program comprised two main activities: Japanese language learning and English language learning, involving students of classes IX A, IX B, and IX C with a total of 83 students. Japanese learning focused on cultural introduction, hiragana writing, and self-introduction sentences (Jikoshoukai), while English learning focused on notice text material and its linguistic features. Methods employed included lectures, demonstrations, question-and-answer sessions, and interactive quizzes. Results showed high enthusiasm from students, evident from their active participation throughout the learning process. This activity is expected to broaden students' interest in foreign languages and encourage multilingual competence development from an early age.